A Novel LEC Framework Incorporating Source Resolution: Spatiotemporal Evolution and Multi-Scenario Prediction of Soil Heavy Metal Risks - Xiufang Zhao; Kang Hou; Yujie Zhu; Xiaoping Li; Zeyu Liu; Xinyuan Zhu; Ruochen Mei; Luohong Zhang; Xuxiang Li (Journal of Environmental Chemical Engineering, 2026)

A multi-model fusion framework for assessing microscale carbon stock dynamics and ecological quality regulation - Ruoxi Li; Kang Hou; Yuxiang Xue; Bo Zhang; Ruochen Mei; Zhao Liu; Xuxiang Li (Environment, Development and Sustainability, 2026)

Estimation and inference of multi-effect generalized geographically and temporally weighted regression models - Zhi Zhang; Ruochen Mei; Changlin Mei (Spatial Statistics, 2024)

Study on the spatial-temporal differences and evolution of ecological security in the typical area of the Loess Plateau - Jiafeng Wen; Kang Hou; Haihong Li; Yue Zhang; Dan He; Ruochen Mei (Environmental Science and Pollution Research, 2021)

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.

Tree‐ring‐based precipitation reconstruction in the source region of Weihe River, northwest China since AD 1810 - Changfeng Sun; Yu Liu; Huiming Song; Ruochen Mei; Paramate Payomrat; Lu Wang; Ruoshi Liu (International Journal of Climatology, 2018)
A tree‐ring width chronology of Picea purpurea Mast from Mt. Shouyang in the source region of Weihe River (SWR), northwest China, was developed in this study. Correlation analysis showed that the precipitation from previous August to current July was the limiting climate factor of tree growth. Using a reliable and stable linear regression model, which explained 42.6% of the variance of the actual precipitation during the calibration period from 1958 to 2014, a 205‐year long precipitation series was reconstructed for the SWR. The dry years in the reconstruction were well supported by historical documents, and famous historical droughts were also recorded in the dry periods of a low‐frequency scale of the reconstructed precipitation. As demonstrated by the spatial correlation patterns, the reconstructed series compared well with other hydroclimate records for northwest China, indicating that it could represent large‐scale hydroclimate changes. The 2–8‐year interannual cycles and the interdecadal quasiperiods of 15.9 years and 18.6 years revealed that the precipitation in this region was probably affected by the El Niño‐Southern Oscillation and North Atlantic Oscillation. The dry/wet years corresponded well with the El Niño/La Niña events and the SWR commonly experienced droughts during the low periods of North Atlantic Oscillation.

Interannual variability of PDSI from tree-ring widths for the past 278 years in Baotou, China - XinJia Zhang; Yu Liu; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Trees, 2017)

Tree-ring-width-based PDSI reconstruction for central Inner Mongolia, China over the past 333 years - Yu Liu; Xinjia Zhang; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Climate Dynamics, 2017)